ETOS MASYARAKAT UTAMA - Hidayat, Komaruddin (Jurnal Bestari, 1992)
The concept of ideal society is a kind of sociological and empiricall phenomena. Muhammadiyah, the gretest modeern Islamic organization, should be considered as an organ which struggles to establish Islamic ideal society which Muhammadiyah will actulize must be based on the principles of monotheism and humanism